Brief psychological intervention for distress tolerance in an adult secondary care community mental health service: an evaluation. (12th November 2020) - Wright, Isobel; Travers-Hill, Emma; Gracey, Fergus; Troup, Jordan; Parkin, Katherine; Casey, Stephanie; Kim, Youngsuk
Abstract: Distress intolerance has been suggested to be a maintaining factor in several mental health conditions. Distress tolerance skills training has been found to be beneficial in emotionally unstable personality disorder (EUPD) and post-traumatic stress disorder (PTSD). Short-term targeted interventions are increasingly being implemented in response to demand. This study investigates the efficacy of a distress tolerance brief psychological intervention (DT BPI) delivered by non-psychologists within an adult secondary care mental health service. Questionnaire data (pre and post) are reported from 43 participants who completed the intervention. Results suggest that the intervention was associated with significant improvements in distress tolerance, mood, anxiety and wellbeing. This indicates that a DT BPI can be effective when delivered by non-psychologists to real-world adult secondary care clients. The findings offer promising evidence that DT BPI could be a beneficial, cost-effective intervention and warrants further large-scale investigation. Key learning aims: (1) To enhance practitioners' awareness of distress intolerance as a potential maintaining factor and therefore treatment target. (2) To outline a transdiagnostic distress tolerance brief psychological intervention. (3) To illustrate the potential of this distress tolerance brief psychological intervention to produce positive reliable change with real-world clients when delivered by non-psychologists.